Determinants of Teacher Competence in Islamic Education: Bibliometric Analysis and Approach - Fadli Agus Triansyah; Yusupov Komaliddin Bakhtiyor Ugli; Ilham Muhammad; Nurhoiriyah Nurhoiriyah (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
This study aims to identify publications on teacher competence in madrasah education and describe this research's characteristics. The bibliometric analysis method was used in this study. The results showed that publications on teacher competency in madrasahs/schools increased yearly from 2017 to 2020. The highest number of documents was at the institution or university "Sunan Kalijaga State Islamic University Yogyakarta" with six documents, in the journal "JIP Scientific Journal PGMI" with 85 documents, and one article in the Journal of Research and Thought on Islamic Education (JRTIE) entitled "Strengthening new literacy for primary school teachers in responding to the challenges of the industrial revolution era 4.0". The focus of the first research was observation and management. The second research focus was social competency and teacher competency. The third research focus was development and implementation. The new theme keywords are planning, preparation, elementary school, and lesson plan. That is, the keywords with the latest theme can be used as a novelty for further research that wants to research related to this field.